“A Rare Case of Post-Tuberculosis Proximal Tracheal Stenosis with Suspected Tracheobronchial Mycosis: Case Report” - Nyoman Adi Tenaya; Wayan Wahyu Semara Putra (Jurnal Impresi Indonesia, 2026)
Tuberculosis (TB) is one of the leading causes of death due to infectious diseases worldwide. Indonesia ranks second in global TB cases according to the 2024 TB report. Although TB treatment successfully cures most patients, post-TB complications in the respiratory tract can occur. Tracheal stenosis as a sequel to TB is a rare manifestation and often resembles asthma or other obstructive lung diseases. In addition to structural causes, opportunistic infections such as tracheobronchial mycosis should be considered. A 37-year-old man presented with progressive shortness of breath, wheezing, and a sensation of obstruction in the throat. The patient had a history of pulmonary TB, which was fully treated in 2016. Physical examination revealed wheezing in both lung fields, and a chest X-ray showed signs consistent with TB sequelae. Bronchoscopy revealed partial proximal tracheal stenosis accompanied by suspected tracheobronchial fungal infection. The patient received bronchodilator therapy, corticosteroids, and antifungal treatment, with clinical improvement within four days.